PENGARUH TERAPI TERTAWA TERHADAP TINGKAT KECEMASAN PADA LANJUT USIA DI UPTD GRIYA WERDHA SURABAYA - Umamah, Farida; Mufarrihah, Nazula (Jurnal Ilmiah Kesehatan (Journal of Health Sciences), 2018)
The influence of an aging process experienced by elderly led to various problems such as physically, mental, and social economic. One of the psychological problems experienced by the elderly is anxiety. The purpose of this study is to find the influence of laugh therapy at the level of anxiety on elderly at the UPTD Griya Werdha Surabaya. This research using pre-experimental design by the approach one group pra-post test design, the amount of the sample 33 elderly aged 60-74 years, uses probability sampling by the simple random sampling technique. The independent variable is laugh therapy and the dependent variable is the extent of anxiety on elderly. Uses a DASS 42 questionnaire 42 (Depression Anxiety Stress Scale), analyzed by Wilcoxon sign test. The research results show before it was given laugh therapy most of 17 respondents (51,5 % ) is having moderate anxiety and after having given laugh therapy obtained almost entirely 30 respondents ( 90,9 % ) is having mild anxiety. The results of the analysis ρ=0,000 where ρ=0,000 means h0 rejected. It means there are the influence of laugh therapy on the level of anxiety on elderly at the UPTD Griya Werdha Surabaya. The conclusions from the study, laugh therapy is able to reduce the anxiety on the elderly. Hopefully the nurse will continue the laugh therapy at UPTD Griya Werdha Surabaya, so that elderly motivated to do this activity regularly and gather.